ANALISIS SISTEM AKUNTANSI PENJUALAN KREDIT PADA PDAM WAY RILAU KOTA BANDAR LAMPUNG: ANALISIS SISTEM AKUNTANSI PENJUALAN KREDIT PADA PDAM WAY RILAU KOTA BANDAR LAMPUNG - Mulyani, Adinda Safitri; Wardianto, K. Bagus (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
Technological developments are currently progressing by using technology in managing company operational activities. Computerization provides access for all of the company's operational activities, one of which is the Credit Sales System at PDAM Way Rilau, Bandar Lampung City. This study discusses the problems that exist in the company, namely how the credit sales accounting system flows and whether the credit sales accounting system at PDAM Way Rilau, Bandar Lampung City has been running optimally. This study aims to determine the functions involved in the credit sales accounting system at PDAM Way Rilau, and to determine the current flow of the sales recording system at PDAM Way Rilau. The type of research used is descriptive qualitative research, with data collection methods used are interviews and documentation. The data analysis technique used is data reduction, data presentation, and verification. The results showed that the credit sales accounting system at PDAM Way Rilau, Bandar Lampung City in the field was in accordance with the SOP but was less efficient and did not run optimally. This is because the operational procedure process is too long and a waste of time, as in the credit approval procedure for filling out forms, it is done repeatedly, namely by manual and system. In addition, the procedure for procuring goods was too long, resulting in a run out of goods (empty) and resulted in a delay in the connection installation process. In the end, the customer has to wait a long time until the goods are available again in the warehouse.